PROBLEMS IN TRANSLATING PHRASEOLOGICAL UNITS FROM GERMAN INTO UZBEK - Shukhratkhon, Imyaminova (International Journal of Psychosocial Rehabilitation, 2020)
The following article is devoted to the issues of translating phraseological units from German into Uzbek. The article highlights the role of phraseological units in the language and emphasizes the importance of taking into account the customs and mentality of two nations while translating.